Effects of voluntary and evoked locomotor muscle fatigue on respiratory responses to a high intensity interval training session - Pageaux, B.; Assadi, H.; Theurel, J.; Lepers, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: High intensity interval training (HIIT) is a time-efficient training method to improve aerobic capacities. In the present study, we tested the impact of pre-fatiguing the locomotor muscles on respiratory responses to a HIIT session. As muscle fatigue can be induced by evoked (electromyostimulation, EMS) or voluntary (VOL) contractions, we also tested whether EMS fatigue and VOL fatigue could differently impact respiratory responses to a HIIT session. As EMS contractions involve a different muscle fibbers recruitment pattern and higher respiratory responses than VOL contraction (Maffiuletti 2010), we hypothesised than EMS fatigue would have the greater impact on respiratory responses to a HIIT session. Methods: Fifteen subjects completed a control session, an EMS fatigue session and a VOL fatigue session. Each session consisted in the completion of a running intermittent time to exhaustion test (30-30, 30s run interspaced by 30s rest) performed at the speed eliciting VO2max. Subjects were pre-fatigued with EMS or VOL contractions. The EMS fatigue protocol consisted in 30 bilateral intermittent isometric evoked contractions of the knee extensors. In the VOL session, subjects performed as many bilateral intermittent maximal isometric voluntary contractions (MVC) of the knee extensors as necessary to induce the same decrease in force experienced following the EMS fatigue protocol. Respiratory parameters were collected during the 30-30. Results: Time to exhaustion decreased in both fatigue conditions with a greater decrease following the EMS fatigue compared to the VOL fatigue. This decrease in time to exhaustion was associated with a decrease in absolute time spent above 90% VO2max (t90). When normalised by the performance of each respective session, the relative t90 decreased only during the VOL fatigue session. Both fatigue protocols induced an increase in respiratory responses to the exercise. Interestingly, higher VO2, respiratory frequency and ventilation was observed during the EMS fatigue session compared to the control and VOL fatigue session. Discussion: Both pre fatigue protocols induced an increase in respiratory responses to the exercise, leading to a decrease in time to exhaustion. Interestingly, due to the greater respiratory responses, only the absolute t90 and not the relative t90 was altered by the EMS fatigue. Future research should aim to investigate whether integrating pre-fatigue of the locomotor muscles induced by EMS before completion of a HIIT session could have beneficial long term effects for athletes and patients.